Maximizing the benefits of global business services the shared services model - Softić, Omer; University of Santo Tomas Publishing House (Manila University of Santo Tomas Publishing House, 2019)
This book proposes a five-step approach that is necessary to achieve the objectives of shared services. It also introduces five levers that are vital for maximising the financial and non-financial benefits available in the country, at both regional and global levels. These levers have been continuously supported by extensive ongoing research and industry experiences across Europe and Asia. Furthermore, knowledge from industry professionals over the past two decades, combined with case studies, reveals new insight into tools, approaches and experiences that will guide leaders of shared services towards its full and new potential with a greater chance of success.
Chapter 1. Introduction to Shared Services
Chapter 2. The Current Shared Services Landscape
Chapter 3. Framework for Value Creation
Chapter 4. Critical Steps for Implementation of Shared Services
Chapter 5. Benefits of Shared Services
Chapter 6. Chargeback
Chapter 7. A Case Study of FSSC in the European Union
Chapter 8. The Asian Perspective
Chapter 9. Trends in SSC
Chapter 10. Philippines as a Global Hub
Chapter 11. Building A Career in Shared Service
Errata slip tipped in at end.
Includes bibliographical references (pages 131-136) and index.
Keywords: Shared services (Management) -- Philippines; Shared services (Management) -- Asia; Service industries -- Philippines; Service industries -- Asia